Electron fluxes and pitch‐angle distributions at dipolarization fronts: THEMIS multipoint observations. Issue 2 (25th February 2013) - Runov, A.; Angelopoulos, V.; Gabrielse, C.; Zhou, X.‐Z.; Turner, D.; Plaschke, F.
Abstract: [1] Taking advantage of multipoint observations from a Cluster‐like Time History of Events and Macroscale Interactions during Substorms (THEMIS) probe configuration repeated in three events, we study pitch‐angle distributions (PAD) of lower energy (0.2–keV) electrons and omnidirectional energy‐time spectrograms of higher energy (30–500 keV) electrons observed at and near dipolarization fronts in the plasma sheet. Recent observations have shown that dipolarization fronts in the plasma sheet provide an impulsive electric field suggested to cause electron energization and dispersionless injections. Increase and decrease in energetic electron flux are equally probable at the fronts, however. Our case studies demonstrate increased energetic electron flux in the front's central region but decreased flux on its dusk side, where diverted plasma flow forms a vortex. An electric field associated with this vortex causes the electron flux decrease. We also find that shorter‐term energetic flux decreases, often observed before injections, coincide with a dip in the northward magnetic field ahead of the front. We attribute these decreases to particle energy loss via the inverse betatron effect. Our case studies reveal that pancake‐type (maximum at 90° pitch angle) and cigar‐type (maxima at 0 and 180°) PADs coexist at the same front. Our data analysis suggests that energetic electron PADs are mainly pancake type near the neutral sheet (| B x | < 5 nt) and mainly cigar type at | B x | > 10 nt. These results, to be confirmed in statistical studies, provide important constraints for further modeling of electron energization and transport toward the inner magnetosphere. Key Points: Observations of pitch‐angle distributions with repeated probe configurations Electron flux variations depend on probe relative to the flow type of electron PAD depends on position relative to the neutral sheet